Sustainable alternative of palm wine analogue from different tiger nut milk-sugar syrup blends for local production - Adindu O. Onyeodili; Gabriel I. Okafor; Chigozie F. Okoyeuzu; Onyekachukwu Chukwuebuka Nduka; Queency N. Okechukwu; Mouandhe Imamou Hassani; Szymon Juchniewicz; Katarzyna Leicht; Charles Odilichukwu R. Okpala; Małgorzata Korzeniowska; Raquel P.F. Guiné (Exploration of Foods and Foodomics)
Aim: The unfermented pale-yellow exudates (“palm sap”) emerge from tapped unopened spathe of mostly oil palm (Elaeis guineensis) and raphia palm (Raphia hookeri). Besides, tiger nut milk (Kunuaya) is among the non-alcoholic refreshing drinks with dairy appearance. A sustainable alternative could therefore emerge from blends of tiger nut milk and sugar syrup to serve a resembling role as palm wine. In this context, therefore, palm wine analogue from different tiger nut milk and sugar syrup blends using palm wine dreg as inoculum was evaluated by proximate, physicochemical, microbial, and sensorial analyses at different time intervals. Methods: The materials were processed, analyzed, and packed using standard referenced procedures. This required freshly tapped palm sap juxtaposed with blends of tiger nut milk-sugar syrup beverage, and thereafter subjected to aerobic fermentation. Importantly, the tiger nut milk-sugar syrup medium has been pitched with palm wine dreg (inoculum source) between fermentation time 26–30 h, and temperature 29.8°–32°C. Results: Considering all the analytical outcomes, from proximate, microbiological, physicochemical, to sensory data, the control appeared to somewhat resemble those of the experimental samples of this study. Conclusions: Potentially, the (palm wine) analogue produced from tiger nut milk and sugar syrup blends using (palm wine) dreg as inoculum could be embraced by the market as natural palm wine. Indeed, the emergent product should serve as an alternative sustainable promise for palm wine, which could help fill the market supply gap, especially in the seasons of reduced supply/yield.